2006
DOI: 10.1007/s00431-006-0330-x
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis and acute renal failure in a child with Salmonella enteritidis gastroenteritis

Abstract: We report on an 11-year-old boy who developed rhabdomyolysis and acute renal failure following Salmonella enteritidis gastroenteritis. Rhabdomyolysis should be considered as a potentially fatal complication in patients with Salmonella gastroenteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“… 10 , 11 Previous literature reported that renal injury was more prominent in cases of rhabdomyolysis induced by typhoidal and nontyphoidal Salmonella . 12 , 13 In our present case, there was evidence of multiorgan damage to the liver, myocardium, and rhabdomyolysis. The elevated levels of CK (maximum peak: 729,869 U/L) and myoglobin (> 3,000 ng/mL) were particularly pronounced compared with previously reported cases of rhabdomyolysis induced by nontyphoidal Salmonella , 14 although the renal injury in our case was not as prominent.…”
Section: Discussionsupporting
confidence: 50%
“… 10 , 11 Previous literature reported that renal injury was more prominent in cases of rhabdomyolysis induced by typhoidal and nontyphoidal Salmonella . 12 , 13 In our present case, there was evidence of multiorgan damage to the liver, myocardium, and rhabdomyolysis. The elevated levels of CK (maximum peak: 729,869 U/L) and myoglobin (> 3,000 ng/mL) were particularly pronounced compared with previously reported cases of rhabdomyolysis induced by nontyphoidal Salmonella , 14 although the renal injury in our case was not as prominent.…”
Section: Discussionsupporting
confidence: 50%
“…There are only scarce reports describing renal abscess formation in the course of NTS infection (8), but according to our knowledge, this is the first report describing the occurrence of ARF mostly caused by acute NTS pyelonephritis per se in children. On the other hand, ARF caused by severe dehydration, shock or rhabdomyolysis has already been reported in the course of salmonella infection (10,11). Besides the disruption of tubular function by interstitial infiltrates of neutrophils and phagocytes, interstitial oedema, tubular obstruction by cellular debris and intrarenal vasoconstriction usually described as possible aetiologies of ARF in pyelonephritis (13), the direct toxic effect of salmonella on the kidney with generalized kidney tissue involvement which was shown by DMSA and mild hypovolaemia were probably contributing factors to ARF in our patient.…”
Section: Discussionmentioning
confidence: 97%
“…In general, abscess formation and acute renal failure (ARF) are very rarely described in the course of acute pyelonephritis caused by any microbes (6). Renal abscess formations were only occasionally reported in the course of NTS infection (7–9), while ARF after NTS infection has been described even more rarely, and mostly results from frank dehydration, shock or rhabdomiolysis (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The bulk of prior reported cases were in Japanese children, which may be a consequence of diets in which raw meats and fish are consumed. 6 The patient presented here is one of the few cases presenting in the Western hemisphere and represents the first reported pediatric case of Salmonellainduced rhabdomyolysis and renal failure, successfully managed without the use of dialysis. S heidelberg is relatively uncommon but is considered a more invasive strain relative to other Salmonella species.…”
Section: Discussionmentioning
confidence: 89%